99mTc-MAA Scintigraphy for Assessing Hepatic Arterial Infusion Pump: The Rate Being a Snare - Hari, Adithya; Jacobs, Justin; Chhabra, Shalini; Grewal, Ravinder K. (World Journal of Nuclear Medicine, 2025)
For liver-directed parenteral therapies in cholangiocarcinoma and colorectal liver metastases, the hepatic arterial infusion pumps (HAIPs) are used to maximize the drug concentrations within the malignant tumors. The patency and normal functioning of the HAIP system is assessed by radionuclide imaging with 99mTc-MAA. We bring forth a relatively rare instance where the rate of infusion of the radiopharmaceutical determines the appearance of the hepatogram in the scan.
Keywords: 99mTc-MAA; hepatic arterial infusion pump; liver-directed therapy